Studies on Pyrimidines, Part II: Synthesis and Antibacterial Activity of 7-(2'-hydroxy-5'-methylphen-1'yl)-2-aceyl-5-substituted phenyl-3-oxo-2,3,4,4-tetrahydeothiazolo (3,2-a)-pyrimidines - Champaneri, H.R.; Modi, S.R.; Naik, H.B. (Asian Journal of Chemistry, 2010)
The title compounds have been prepared by heating pyrimidine-2-thiones with chloroacetic acid in acetic acid/acetic, anhydride in the presence of sodium acetate. These compounds were screened for antibacterial activity.